The role of Islamic education in Care of the elderly Analytical descriptive study (Journal of the College of Basic Education, 2022)
The basic pillars of Islamic education are caring for society as a whole, and the last of this is caring for parents to see parents benevolently, because Islam in its paths, foundations and jewels cares about this legitimacy from society alone. Islamic education focused in all its components on this important legitimacy in the Arab Islamic society.The problem of the study: The problem of this study lies in the extreme importance of caring for the social Sharia, which was once effective and now in a deplorable state. The researcher studies this education and the permissibility of Islamic education in caring for the elderly.This study aims to identify the problem of the elderly and the role of Islamic education in caring for these people as a social segment that has its own characteristics and the structure of its personalities. As well as the definition of methods of care for these elderly.